GNSS carrier phase-based attitude determination - Giorgi, G.; Teunissen, Peter (InTech, 2012)
Attitude determination through the use of Global Navigation Satellite System (GNSS) signals is one of the many applications of satellite-based navigation. Multiple GNSS antennas installed on a given platform are used to provide orientation estimates, thus adding attitude information to the standard positioning service. Precise attitude estimates are obtained by exploiting the higher ranging resolution of the carrier phase observables, which are of two orders of magnitude more accurate than pseudorange measurements. However, each carrier phase measurement is ambiguous by an unknown integer number of cycles. Carrier phase integer ambiguity resolution is the key to high-precision GNSS positioning, navigation, and attitude determination. It is the process of resolving the unknown cycle ambiguities of the carrier phase data as integers. After ambiguity resolution, precise baseline estimates become available, which can be used to derive the attitude of a platform equipped with multiple antennas. The purpose of this contribution is to present, analyze and test a novel ambiguity estimation and attitude determination method.The ambiguity-attitude estimation method given and analyzed in this work is an implementation of the constrained integer-least quares, an extension of the well-known least-squares method applied to systems whose parameters are subject to mixed constraints. The key to this new method is an extension of the popular LAMBDA method: the multivariate constrained LAMBDA method. The method estimates the integer ambiguities and the platforms attitude in an integral manner, fully exploiting the known body geometry of the multi-antenna configuration by means of multiple geometrical constraints. As a result, the ambiguity resolution performance is greatly improved, and the reliability of the GNSS-based attitude solution is enhanced. The method is extensively analyzed from a theoretical standpoint, and thoroughly tested with a wide range of test scenarios, from simulations to high-dynamic flight experiments.